The Effect of a Sibling's Gender on Earnings, Education and Family Formation - Noemi Peter; Petter Lundborg; Dinand Webbink (Institute for the Study of Labor (IZA), 2015)
We examine how the gender of a sibling affects earnings, education and family formation. Identification is complicated by parental preferences: if parents prefer certain sex compositions over others, children's gender affects not only the outcomes of other children but also the very existence of potential additional children. We address this problem by looking at dizygotic twins. In these cases, the two children are born at the same time, so parents cannot make decisions about one twin based on the gender of the other twin. We find that the gender of the sibling influences both men and women, but in a different way. Men with brothers earn more and are more likely to get married and have children than men with sisters. Women with sisters obtain lower education and give birth earlier than women with brothers. Our analysis shows that the family size channel cannot explain the findings. Instead, the most likely explanation is that siblings affect each other via various social mechanisms.
Keywords: J00; J24; J16; 330; sibling gender; sex composition; twins; income; schooling; fertility